Recognition of fold- and function-specific sites in the ligand-binding domain of the thyroid hormone receptor-like family - Verma, Sonia; Chakraborti, Soumyananda; Singh, Om P.; Pande, Veena; Dixit, Rajnikant; Pandey, Amit V.; Pandey, Kailash C. (Frontiers in Endocrinology, 2022)
Background: The thyroid hormone receptor-like (THR-like) family is the largest transcription factors family belonging to the nuclear receptor superfamily, which directly binds to DNA and regulates gene expression and thereby controls various metabolic processes in a ligand-dependent manner. The THR-like family contains receptors THRs, RARs, VDR, PPARs, RORs, Rev-erbs, CAR, PXR, LXRs, and others. THR-like receptors are involved in many aspects of human health, including development, metabolism and homeostasis. Therefore, it is considered an important therapeutic target for various diseases such as osteoporosis, rickets, diabetes, etc. Methods: In this study, we have performed an extensive sequence and structure analysis of the ligand-binding domain (LBD) of the THR-like family spanning multiple taxa. We have use different computational tools (information-theoretic measures; relative entropy) to predict the key residues responsible for fold and functional specificity in the LBD of the THR-like family. The MSA of THR-like LBDs was further used as input in conservation studies and phylogenetic clustering studies. Results: Phylogenetic analysis of the LBD domain of THR-like proteins resulted in the clustering of eight subfamilies based on their sequence homology. The conservation analysis by relative entropy (RE) revealed that structurally important residues are conserved throughout the LBDs in the THR-like family. The multi-harmony conservation analysis further predicted specificity in determining residues in LBDs of THR-like subfamilies. Finally, fold and functional specificity determining residues (residues critical for ligand, DBD and coregulators binding) were mapped on the three-dimensional structure of thyroid hormone receptor protein. We then compiled a list of natural mutations in THR-like LBDs and mapped them along with fold and function-specific mutations. Some of the mutations were found to have a link with severe diseases like hypothyroidism, rickets, obesity, lipodystrophy, epilepsy, etc. Conclusion: Our study identifies fold and function-specific residues in THR-like LBDs. We believe that this study will be useful in exploring the role of these residues in the binding of different drugs, ligands, and protein-protein interaction among partner proteins. So this study might be helpful in the rational design of either ligands or receptors.